2022
DOI: 10.4102/ajlm.v11i1.1718
|View full text |Cite
|
Sign up to set email alerts
|

Human herpes virus type-6 is associated with central nervous system infections in children in Sudan

Abstract: Background: Human herpes virus type-6 (HHV-6) is increasingly recognised as a febrile agent in children. However, less is known in sub-Saharan African countries, including Sudan.Objective: We investigated the involvement of HHV-6 in paediatric central nervous system (CNS) infections in Khartoum, Sudan.Methods: Febrile patients aged up to 15 years with suspected CNS infections at Omdurman Hospital for Children from 01 December 2009 to 01 August 2010 were included. Viral DNA was extracted from leftover cerebrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This patient was co-infected with HHV-6. [ 20 ] The second case was 14 years old and was admitted after 1 day of symptoms onset. He presented with only fever and headache.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This patient was co-infected with HHV-6. [ 20 ] The second case was 14 years old and was admitted after 1 day of symptoms onset. He presented with only fever and headache.…”
Section: Resultsmentioning
confidence: 99%
“…The overall clinical, nucleic acids and conventional microbial findings are illustrated in Figure 1 which describes findings from this study alongside findings reported in our other publications. [17,20,21]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations